2009
DOI: 10.1007/s12015-009-9103-z
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a ROCK Inhibitor in Extracellular Matrix Supports More Undifferentiated Growth of Feeder-Free Human Embryonic and Induced Pluripotent Stem Cells upon Passaging

Abstract: Optimization and development of better defined culture methods for human embryonic and induced pluripotent stem cells (hESCs and hiPSCs) will provide an invaluable contribution to the field of regenerative medicine. However, one problem is the vulnerability of hESCs and hiPSCs to apoptosis that causes a low plating efficiency upon passaging. Herein, we have developed a novel hESCs and hiPSCs culture technique that uses ROCK inhibitor (ROCKi) Y-27632 (10 microM) in Matrigel-coated dishes in both serum- and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 57 publications
1
65
0
Order By: Relevance
“…Recent published work has demonstrated the ability of human cells (e.g., keratinocytes and airway epithelial cells) to proliferate indefinitely, without the transduction of exogenous viral or cellular genes, by addition of a pharmacological inhibitor of the Rho kinase signaling pathway (Y-27632, "Y") (19)(20)(21)(22) in the presence of mouse feeder cells (23). These "conditionally reprogrammed cells" were shown to exhibit a stem cell-like phenotype with an up-regulation of adult stem cell genes (e.g., a6/b1 integrin, DNp63a) (24).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Recent published work has demonstrated the ability of human cells (e.g., keratinocytes and airway epithelial cells) to proliferate indefinitely, without the transduction of exogenous viral or cellular genes, by addition of a pharmacological inhibitor of the Rho kinase signaling pathway (Y-27632, "Y") (19)(20)(21)(22) in the presence of mouse feeder cells (23). These "conditionally reprogrammed cells" were shown to exhibit a stem cell-like phenotype with an up-regulation of adult stem cell genes (e.g., a6/b1 integrin, DNp63a) (24).…”
Section: Clinical Relevancementioning
confidence: 99%
“…In contrast to hESC, mES cells do not require ROCK inhibition for survival even when disaggregated to a single cell suspension. Since that initial study, subsequent screens have identified additional ROCK selective inhibitors that promote the survival of hESC (Andrews et al 2010;Pakzad et al 2010) and neural stem cells (Xu et al 2010), thereby independently validating the role of ROCK as a key regulator of ESC survival. The addition of Y27632 to the culture media is now standard practice and has greatly improved the reliability of hES cell survival (Olson 2008;Krawetz et al 2009).…”
Section: Rho Family Gtpases In Embryonic Stem Cellsmentioning
confidence: 93%
“…Interestingly, a single dual-function protein, Abr, acts as Rho-GEF and Rac-GAP within dissociated hES cells in culture, simultaneously activating Rho and inactivating Rac upon cell dissociation, in a manner dependent on cell-cell interactions involving E-cadherin (Martin 1981;Ohgushi et al 2010). The role of E-cadherin in hESC survival was also revealed in a chemical biology screen for small molecules that affected survival (Pakzad et al 2010). One compound increased the survival of dissociated cells by reducing E-cadherin endocytosis, thus increasing the levels of cell-surface E-cadherin and consequently promoting cell-cell adhesions.…”
Section: Rac Signaling In Es Cellsmentioning
confidence: 99%
“…It has been found to support feederfree hESC and hiPSC growth (Pakzad et al, 2010), hESC growth in 3D culture (Chayosumrit et al, 2010), aid cryopreservation (Martin-Ibanez et al, 2008;Baharvand et al, 2010) and is now widely used in hESC growth and manipulation. More survival compounds of greater specificity, equivalent potency and reduced toxicity relative to Y-27632 were discovered in another study (Andrews et al, 2010).…”
Section: Embryonic Stem Cell Survivalmentioning
confidence: 99%